2016
DOI: 10.1111/ecoj.12290
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Way Capital Flows and Global Imbalances

Abstract: This article shows how underdeveloped financial markets in emerging economies can explain the pattern of two-way capital flows between emerging economies (such as China) and the developed world (such as the United States). Our calibrated model reproduces China's rising financial capital outflows and FDI inflows as well as its massive trade imbalances in recent decades. Our model also predicts that global trade imbalances may be sustainable even in the long run and the conventional wisdom that the 'saving glut'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…(Bernanke 2005. ) There is a vast theoretical literature that considers differences in financial development as the main driver of global current account imbalances (see, e.g., Angeletos andPanousi (2011), Benhima (2013b), von Hagen and Zhang (2014) as well as Eugeni (2015) which are closely related to Caballero et al (2008) and/or to Mendoza et al (2009), Ju andWei (2010) as well as Wang et al (2017) which model two-way capital flows, and Coeurdacier et al (2015) which provides microfoundations for the emergence of a global saving glut.) 18 To summarize, these theoretical papers suggest that capital market imperfections and heterogeneity in financial development are central to explaining stylized facts 1, 2 and 6.…”
Section: Heterogeneity In Financial Developmentmentioning
confidence: 99%
“…(Bernanke 2005. ) There is a vast theoretical literature that considers differences in financial development as the main driver of global current account imbalances (see, e.g., Angeletos andPanousi (2011), Benhima (2013b), von Hagen and Zhang (2014) as well as Eugeni (2015) which are closely related to Caballero et al (2008) and/or to Mendoza et al (2009), Ju andWei (2010) as well as Wang et al (2017) which model two-way capital flows, and Coeurdacier et al (2015) which provides microfoundations for the emergence of a global saving glut.) 18 To summarize, these theoretical papers suggest that capital market imperfections and heterogeneity in financial development are central to explaining stylized facts 1, 2 and 6.…”
Section: Heterogeneity In Financial Developmentmentioning
confidence: 99%
“…Wang, Weh, and Xu () point to a “two way capital flow puzzle”: fixed capital flows from rich to poor countries, whereas financial capital flows in the opposite direction. They augment a neoclassical growth model with two wedges: one that distorts firms’ investment decisions and another that distorts households’ saving decisions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Jeanne and Rancière (2011) and Bacchetta, Benhima, and Kalantzis (2013) found that neither the precautionary motive against aggregate shocks nor the presence of idiosyncratic shocks can explain international reserve accumulation in China. Wang, Weh, and Xu (2015) point to a "two way capital flow puzzle": fixed capital flows from rich to poor countries, whereas financial capital flows in the opposite direction. They augment a neoclassical growth model with two wedges: one that distorts firms' investment decisions and another that distorts households' saving decisions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, most of the literature devoted to financial markets and the allocation of capital has focused on the Lucas (1990) paradox, namely the lack of capital flows from rich to poor countries that are expected to offer higher returns. The observed upstream capital flows and global imbalances, amounting to 0.62% of world GDP on average over the last decade, 4 have led to explanations rooted in differences in public expenditure [Eugeni (2015)], in time preference [Aglietta et al (2002[Aglietta et al ( , 2007], in financial rigidities [Song et al (2011), Reinhardt et al (2013), Coeurdacier et al (2015)], or in asset riskiness (Gourinchas and Jeanne (2013), Alfaro et al (2014), Wang et al (2015)]. Wang et al (2015) suppose a higher risk-free interest rate in developed economies.…”
mentioning
confidence: 99%